A Study of Character Design Development from Pingchang Puppetry for the New Generation - Xie, Cheng; Aungkavipart, Apichaya (วารสารดีไซน์เอคโค, 2026)
Pingchang Puppetry is an ancient, handcrafted rod-puppet theatre rooted in the sacrificial rituals of Meishan Wunuo culture, yet it faces growing challenges in engaging younger audiences within contemporary digital media environments. This study focuses on design translation: converting the cultural and visual resources of Pingchang Puppetry into a modern character system that is readable, recognizable, and suitable for cross-media communication. Using field visits and semi-structured interviews with a local inheritor, the study document’s role archetypes, costume structures, representative colors, decorative motifs, and performance features, and then restructures them into a usable element framework for character development. In parallel, a comparative visual analysis of wellknown animation IP familiar to younger audiences is conducted to extract contemporary preference cues in proportion, facial feature simplification, color organization, and identitymarker reduction. These two sets of findings are synthesized into an operational design strategy and applied to the creation of a serialized three-character IP system. As design outcomes, the study produces modern character concept schemes, corresponding 3D character prototypes, and a preliminary visual identity and logo concept for media dissemination. Expert interviews are further used to refine silhouette stability, symbol clarity, color hierarchy, and expression readability, improving consistency and adaptability across applications. The study therefore delivers both tangible design outputs and a reusable workflow from cultural element extraction to contemporary character generation for intangible cultural heritage revitalization.